Inovasi Digital Pemuda dalam Menjaga Tradisi Melalui Pengembangan Sholawat Kontemporer - Nurizkya, Azhara; Wahyuni, Lilik; Arthania, Nesia Neo; Purnama, Putri Dewi Intan (Faculty of Cultural Studies, Universitas Brawijaya, 2025)
Ngingrim Hamlet in Pandanrejo Village, Malang Regency, has a rich tradition of sholawat but faces preservation challenges in the digital era due to low technological literacy and lack of documentation. This service activity aims to identify, develop, and optimize the potential of local culture through a digital innovation approach, especially the development of contemporary sholawat as a medium for preserving and promoting religious traditions. The benefits of the service include increasing community digital literacy, active participation of youth in cultural content production, and expanding the reach of da'wah through digital platforms such as YouTube and Instagram. The activity design includes local potential mapping, technical content production training, creative mentoring, and participatory content publication. The results showed that the digitalization of contemporary sholawat succeeded in increasing the involvement of the younger generation, expanding the audience, and creating economic impact through content monetization, despite facing constraints of limited resources and digital literacy. The conclusion of this activity emphasizes that youth engagement, strengthening digital literacy, and multi-stakeholder collaboration are the keys to successful adaptive and sustainable cultural transformation in the modern era.